2017
DOI: 10.3389/fmicb.2017.01529
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Chromium and Uranium Toxicity in Pseudomonas stutzeri RCH2 Grown under Anaerobic Nitrate-Reducing Conditions

Abstract: Chromium and uranium are highly toxic metals that contaminate many natural environments. We investigated their mechanisms of toxicity under anaerobic conditions using nitrate-reducing Pseudomonas stutzeri RCH2, which was originally isolated from a chromium-contaminated aquifer. A random barcode transposon site sequencing library of RCH2 was grown in the presence of the chromate oxyanion (Cr[VI]O42−) or uranyl oxycation (U[VI]O22+). Strains lacking genes required for a functional nitrate reductase had decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Macrolides, such as clarithromycin, are key drugs for treatment of MAC infections. The development of clarithromycin resistance, that makes the therapy prone to fail [ 56 ], has been mainly attributed to mutational alterations of the 23S rRNA gene and to overexpression of EPs [ 15 ]. In particular, the upregulation of EP activity, induced upon drug exposure, can significantly decrease the intracellular concentration of clarithromycin, reducing its clinical efficacy.…”
Section: Mycobacterium Avium Complex (Mac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Macrolides, such as clarithromycin, are key drugs for treatment of MAC infections. The development of clarithromycin resistance, that makes the therapy prone to fail [ 56 ], has been mainly attributed to mutational alterations of the 23S rRNA gene and to overexpression of EPs [ 15 ]. In particular, the upregulation of EP activity, induced upon drug exposure, can significantly decrease the intracellular concentration of clarithromycin, reducing its clinical efficacy.…”
Section: Mycobacterium Avium Complex (Mac)mentioning
confidence: 99%
“…Infections caused by NTM are often difficult to treat since therapy, that needs the use of a combination drug regimen, is long, expensive, and more toxic and more likely to fail than tuberculosis therapy [ 13 , 14 ]. The highly hydrophobic lipid-rich cell wall constitutes a strong barrier to the penetration of various drugs, representing a major contributor for intrinsic resistance of NTM to many antimicrobial compounds currently available [ 15 ], thus encouraging an urgent need for the development of new drugs for the treatment of mycobacterial infections [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of denitrification rates in saltmarsh sediments, it was reported that initial denitrification rates were inhibited by several metals at 1 g/liter, including Pb, Ni, Cr, Zn, Cu, Fe, and Cd (24). Similarly, whole-genome fitness assays conducted on a model denitrifying organism, Pseudomonas stutzeri RCH2, grown under denitrifying conditions, revealed that disruptions to nitrate reductase and denitrification-related genes resulted in decreased fitness of the organism when grown in the presence of elevated concentrations of several different metals, including Cu, Zn, Cr, and U (39,40). The ORR organisms that we isolated must therefore have molecular and physical mechanisms of metal resistance that allow them to survive in the extreme ORR environment, and the nature of those mechanisms is currently under study.…”
Section: Discussionmentioning
confidence: 98%
“…Data from various studies with model denitrifiers (Giannopoulos et al, ; Olaya‐Abril et al, ; Gaimster et al, ; Gaimster et al, ; Kohlmann et al, ; Thorgersen et al, ) and nitrifiers (Qin et al, ; Cho et al, ; Wei et al, ; Mellbye et al, ; Pérez et al, ; Lu et al, ; Carini et al, ) is available for integration into models. However, soil and aquatic environments host complex microbial communities that could differ substantially in terms of the regulation and activity with respect to their nitrogen‐cycling pathways (Lycus et al, ).…”
Section: Current and Future Methods For Assessing Sources And Sinks Omentioning
confidence: 99%